Cardiovascular risk assessment in patients with retinal vein occlusion. Issue 7 (1st July 2002) - Martin, S C; Butcher, A; Martin, N; Farmer, J; Dobson, P M; Bartlett, W A; Jones, A F
Abstract : Aim: Patients with retinal vein occlusions (RVO) are at increased risk of cardiovascular disease (CVD). The risk of future CVD was determined using the Framingham algorithm and this risk estimate was used to guide decisions about preventative treatment for CVD in RVO patients. Methods: 107 unselected RVO patients were studied. After excluding 18 patients because of age, missing data, or pre-existing cardiovascular disease, the calculated coronary heart disease risks (cCHDR) and calculated cardiovascular disease risks (cCVDR) were calculated on the 89 remaining and compared with both the standardised risk and the published incidence of CHD in England by t test or χ 2 test. Results: The mean 10 year cCVDR was significantly higher than the Framingham standardised risk for all RVOs (20.6% (1.2%) v 15.7% (1.1%), p = 0.009) and female RVOs (17.8% (1.2%) v 12.7% (1.0%), p = 0.022) in particular. The 10 year cCHDR, compared to the actual incidence of CHD in England between the ages of 30 and 74 years, was > 15% in twice as many males than expected (62% v 28%, p <0.0001). This rose to almost six times when cCHDRs greater than 30% were compared (17% v 3%, p = 0.002). There was a fourfold increase in the proportion of female RVO patients with a cCHDR above 15% (40% v 9%, p <0.0001) and at a cCHDR of 30% and above (10% v 0%, p = 0.004). There were also significant differences in the cCHDR between central and branch RVO (both sexes). The branch form of RVO (BRVO) having higher cCHDRs because of systolic hypertension (164.1 (21.6) mm Hg v 149.5 (23.5) mm Hg, p = 0.003) and age (61.7 (8.3) years v 56.7 (10.6) years, p = 0.017). Conclusions: RVO is the presenting complaint in a group of patients at increased risk of CVD and is in agreement with the long term follow up data demonstrating an increased mortality from CVD in patients with RVO. The Framingham algorithm can accurately determine the cCHDR (or cCVDR) to assist the clinician in deciding who to treat in accordance with the Joint British Societies' guidelines, with particular regard to hypertension, lipid lowering, and the use of aspirin therapy.